2021
DOI: 10.3390/jrfm14030129
|View full text |Cite
|
Sign up to set email alerts
|

Crisis and the Role of Money in the Real and Financial Economies—An Innovative Approach to Monetary Stimulus

Abstract: `Financial crisis’ is sometimes regarded as synonymous with `economic crisis’, but this is an oversimplification and risks missing the feedback loops between the financial and real economies. In this paper, the role of money is revisited in the context of distinguishing the real economy from the financial economy. A theoretical framework is developed to explain how endogenous (bank credit) and central bank exogenous (quantitative easing, QE) money creation feed into the real and financial economies. It looks a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…A study of the REC initiative provided the cited authors with evidence of the relationship between spending in the form of complementary currency and the promotion and development of the local economy. A similar aspect is highlighted by the results of a study by Simmons et al (2021), who, drawing on the experience of Italian peer-to-peer lending innovator Sardex and the WIR Bank in Switzerland, showed that the two currencies in question contribute to strong, positive countercyclical growth by enabling the creation of interest-free "peer" loans for the small and medium-sized business sector. The case of Argentina's complementary currency Credito and its important role in reviving the economy and strengthening the importance of so-called provincial public services during the Argentine crisis and the collapse of the official peso currency in 2001 was referred to in his research by Kokabian (2020).…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…A study of the REC initiative provided the cited authors with evidence of the relationship between spending in the form of complementary currency and the promotion and development of the local economy. A similar aspect is highlighted by the results of a study by Simmons et al (2021), who, drawing on the experience of Italian peer-to-peer lending innovator Sardex and the WIR Bank in Switzerland, showed that the two currencies in question contribute to strong, positive countercyclical growth by enabling the creation of interest-free "peer" loans for the small and medium-sized business sector. The case of Argentina's complementary currency Credito and its important role in reviving the economy and strengthening the importance of so-called provincial public services during the Argentine crisis and the collapse of the official peso currency in 2001 was referred to in his research by Kokabian (2020).…”
Section: Discussionmentioning
confidence: 56%
“…Considering the second complementary problem, in the light of the presented results of our own research, as well as those of other authors cited in the paper (cf. : Kokabian, 2020;Simmons et al, 2021), the influence and impact of the complementary currency Zielony in Poland on the formation of attitudes and behaviour of users of the system and the local economy, and thus on the conditions conducive to equalized local development is positive. The complementary currency Zielony influences the development of entities participating in the system, and thus contributes to strengthening local development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are other interesting approaches, such as that used in [30], which logically demonstrate that there is a disconnect between the real and financial economies and that the measure of this disconnect is the misallocation of capital into assets and intangible assets. We agree with this vulnerability factor, which leads to price instability, especially during times of crisis.…”
Section: Literature Reviewmentioning
confidence: 99%